Table of Content - -, (Journal of Arabic Language Sciences and Literature, 2025)
Table of Content:1. The art of analogy in the poetry of Aws bin HajarhDr. Said Obaid Abdullah Al-Wahaibi2. Analysis of Arabic Phonetic Articulation PointMs. Salma Mohammed Al-Mutairi3. Mechanisms of Artistic Imagery in the Poetry Collection Sacrifices of Farewell  by Abdullah BashrahilCo-Prof. Sultan Saeed Abu Dabeel4. The speaker and communicative aids in the Maqamat of Badi al-Zaman al-Hamdhani - The Kufi Maqamat as an exampleMs. Alia Ali Saeed Alketbi ,Dr. Muhammad Hilmi bin Abdullah bin Jaafar5. The sociological aspect of language according in Blaggat Alnisa to Aben Taiffor (280h): The discourse of woman with her husbandMs. Alhanouf Ali Al-Feredi, Prof. Abdul-Lateef Marzouq Al-Solami6. Israelite stories between language and mythCo-Prof. Nada Abdullah Aldaher7. A structural semiotic approach to the Quranic character of Yunus, peace be upon him, and the aesthetics of place in the Quranic storyMr. Mahmoud Jamal Rayyan
Keywords: Journal of Arabic Language and Literature